Laktosa Mempertahankan Daya Hidup Spermatozoa Kambing Peranakan Etawah yang Dipreservasi dengan Plasma Semen Domba Priangan - Ferdinand Souhoka, Demianus; Johan Matatula, Michel; Marlene Mesang-Nalley, Wilmientje; Rizal, Muhammad (Jurnal Veteriner; Vol 10 No 3 (2009))
The purpose of this research was to examine the effect of lactose in Tris extender on theviability of Etawah crossbreed goat spermatozoa which is preserved in the plasma using Prianganram seminal plasma at 3–5oC. Semen was collected using artificial vagina once a week. Freshsemen was divided into four tubes, and centrifuged at 3,000 RPM for 30 min. Supernatant wasremoved and replaced which an equal volume with Priangan ram seminal plasma. Semen in firsttube was diluted with Tris extender-20% egg yolk without lactose (control). Semen in second,third, and fourth tubes were diluted with Tris extender-20% egg yolk and 0.3% (0.3 g per 100 mlextender) (L0.3), 0.6% (L0.6), and 1.2% (L1.2) lactose, respectively. Diluted-semen were stored inrefrigerator at 3–5oC. Quality of diluted-semen including percentages of motile spermatozoa (MS),live spermatozoa (LS), and intact plasma membrane (IPM) were evaluated daily during storage at3–5oC for four days. The data were analyzed by usi analysis of variance (ANOVA). Means werecompared significant difference test at 0.05 significant level. Results of this study showed thatmean volume, colour, consistency, pH, mass activity, spermatozoa concentration, MS, LS,spermatozoa abnormal, and IPM of Etawah crossbreed goat fresh semen were 0.68 ml, cream,thick, 7, ++/+++, 4,148.57 million cell/ml, 70%, 83.89%, 7.12%, and 84%, respectively. Addition oflactose in Tris extender could maintain the quality of semen during preservation. At day-5 ofstorage, the percentages of MS, LS, and IPM for treatment L0.6 (40, 55.6, and 53.8%) weresignificantly (P<0.05) higher than treatment L1.2 (36, 50.2, and 51.8%), treatment L0.3 (34, 51.2,and 48.4%), and control (29, 41.4, and 41.8%). In conclusion, addition of 0.6% lactose in Trisextender is the best dose in maintaining the quality of Etawah crossbreed goat spermatozoa, andcould be maintaining percentage of motile spermatozoa 40% for four days after preserved at 3–5oC.
Keywords: lactose, Priangan ram seminal plasma, spermatozoa viability, PE goat.